2017
DOI: 10.1259/dmfr.20160285
|View full text |Cite
|
Sign up to set email alerts
|

Image quality evaluation of small FOV and large FOV CBCT devices for oral and maxillofacial radiology

Abstract: For limited oral and maxillofacial volume imaging (diameter < 50 mm), the polyvalent small FOV CBCT (2D and three-dimensional imaging) system used in this study could reach performances similar to those of the large FOV CBCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 14 publications
0
12
0
1
Order By: Relevance
“…Also, the use of a small FOV may improve the spatial resolution of CBCT in certain brand devices. 41 Notably, all clinical studies were found to use the periodontal probe as a tool for clinical intrasurgical measurement except for the study by Banodkar et al, 39 who employed an endodontic reamer and digital Vernier calliper for taking this measurement. Compared to the periodontal probe, this novel approach was found to be more accurate in obtaining clinical measurements with an accuracy of up to 0.2mm.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the use of a small FOV may improve the spatial resolution of CBCT in certain brand devices. 41 Notably, all clinical studies were found to use the periodontal probe as a tool for clinical intrasurgical measurement except for the study by Banodkar et al, 39 who employed an endodontic reamer and digital Vernier calliper for taking this measurement. Compared to the periodontal probe, this novel approach was found to be more accurate in obtaining clinical measurements with an accuracy of up to 0.2mm.…”
Section: Discussionmentioning
confidence: 99%
“…Small FOV CBCT (diameter < 50 mm), appropriate for small lesions as endodontic lesions. Large FOV CBCT (diameter > 16 cm), appropriate for extensive diseases, as TMDs ( Dillenseger et al, 2017 ). Images were obtained with the mouth closed and maximum intercuspation.…”
Section: Methodsmentioning
confidence: 99%
“…With different hardware components, like X-ray sources and detectors, used by the different manufacturers for their systems further variations in image quality are introduced 4 . The local tomography at the selected scan settings makes the data interpretation therefore often difficult 5 . For this reason, it was decided to perform a tomography study of the same human donor head with multiple CBCT scanners, each time scanned with a variety of machine settings.…”
Section: Introductionmentioning
confidence: 99%